Penerapan integral tentu terhadap pengaruh lebar cakram dan bentuk kaliper pada pengereman sepeda motor di jurusan otomotif SMK - Muhammad Maskur (Kreasi Pustaka Mandiri (Krestama), 2025)
The application of mathematical material in everyday life is part of the expected curriculum achievement in contextual mathematics learning. One of them is integral learning. The benefits of learning materials for solving everyday life problems can help calculate the area or volume needed. One area where mathematical concepts can be applied is the modification of a motorcycle's braking system. Modifying the braking system is important in maintaining driving safety. In this study, the aim is to determine the effectiveness of the brake system by applying definite integrals to changes in the disc and caliper widths. In addition, to determine the performance results of each change in the width of the disc and changes in the shape of the caliper. In this study, researchers used a qualitative approach. Considering the operational enhancements observed in motorcycle disc brake systems, alterations to the caliper, independent of disc plate modifications, prove more efficacious than adjustments to disc plate width while maintaining the original caliper piston configuration.